2016
DOI: 10.1371/journal.pntd.0004376
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetics of Plasmodium vivax in the Peruvian Amazon

Abstract: BackgroundCharacterizing the parasite dynamics and population structure provides useful information to understand the dynamic of transmission and to better target control interventions. Despite considerable efforts for its control, vivax malaria remains a major health problem in Peru. In this study, we have explored the population genetics of Plasmodium vivax isolates from Iquitos, the main city in the Peruvian Amazon, and 25 neighbouring peri-urban as well as rural villages along the Iquitos-Nauta Road.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 59 publications
11
68
0
Order By: Relevance
“…A recent longitudinal study conducted over 25 different villages (among five study areas) confirmed these findings, showing that study areas along the highway from Iquitos to Nauta (cluster A2 and A3) had higher MOI (1.5–2) than isolated communities with low mobility (cluster A1, A4, and A5). However, H e was high in all communities ( H e 0.66–0.76) 76. On the other hand, in San Carlos, a relatively small and isolated village, at 10 km from the Iquitos–Nauta road, genetic diversity and MOI were constrained ( H e = 0.49, MOI = 1.1) 71,74.…”
Section: Genetic Diversity and Population Structure Of P Vivaxmentioning
confidence: 90%
“…A recent longitudinal study conducted over 25 different villages (among five study areas) confirmed these findings, showing that study areas along the highway from Iquitos to Nauta (cluster A2 and A3) had higher MOI (1.5–2) than isolated communities with low mobility (cluster A1, A4, and A5). However, H e was high in all communities ( H e 0.66–0.76) 76. On the other hand, in San Carlos, a relatively small and isolated village, at 10 km from the Iquitos–Nauta road, genetic diversity and MOI were constrained ( H e = 0.49, MOI = 1.1) 71,74.…”
Section: Genetic Diversity and Population Structure Of P Vivaxmentioning
confidence: 90%
“…To test whether the urban landscape is indeed the main factor driving these differences in genetic drift and gene flow between urban and nonurban populations, many studies have used a landscape genetics approach (Beninde, Feldmeier, Veith, & Hochkirch, ; Delgado‐Ratto et al, ; Thomassen et al, ; Wood et al, ; Yakub & Tiffin, ). This approach allows researchers to identify potential barriers or conduits to gene flow between populations and make inferences about the effects of the landscape on evolutionary processes.…”
Section: Introductionmentioning
confidence: 99%
“…P. vivax population genetic analyses in the South West Pacific region, reveal a modest decline in diversity and increasing population structure with the eastward decline in transmission (Fola et al, 2017;Koepfli et al, 2013;Waltmann et al, 2018). However, a clear signature of significant mLD has been observed at low transmission in several studies suggesting increasingly focal transmission as malaria rates decline, and the increasing contribution of genetically similar relapses as new infections become rarer Batista et al, 2015;Chenet et al, 2012;Delgado-Ratto et al, 2016;Ferreira et al, 2007;Imwong et al, 2007;Iwagami et al, 2012;Noviyanti et al, 2015;Orjuela-Sanchez et al, 2013). P. vivax has higher diversity compared to P. falciparum which is consistent with a longer association with humans (Gilabert et al, 2018;Hupalo et al, 2016;W.…”
Section: Introductionmentioning
confidence: 87%
“…Regional surveys reveal source and sink populations and parasite migration in a country and can help to predict whether and where targeted interventions would be effective and the spatial scale required (Auburn & Barry, 2017;Koepfli & Mueller, 2017). Fine-scale population genetic surveys also identify local drivers contributing to sustained transmission such as particular human social and economic interactions Delgado-Ratto et al, 2016;Koepfli & Mueller, 2017). While parasite population genetics and genomics is becoming more popular and accessible, the impact on control programs has been limited, and to date few studies have systematically assessed the long-term impact of malaria control using these approaches (Batista, Barbosa, Da Silva Bastos, Viana, & Ferreira, 2015;Bei et al, 2018;Branch et al, 2011;Chenet, Taylor, Blair, Zuluaga, & Escalante, 2015; R. F. Daniels et al, 2015;Gatei et al, 2010;Gunawardena, Ferreira, Kapilananda, Wirth, & Karunaweera, 2014;Iwagami et al, 2012;Salgueiro, Vicente, Figueiredo, & Pinto, 2016;Vardo-Zalik et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation